WWSD: What Would Socrates Do? The modern dilemma of obedience (Groundings Undergraduate, 2008)
“This is for your own good” is often the aphorism of governments and social institutions in their claims upon our freedoms. Our obedience is framed as collective self-preservation, but can it ever be so simple? Yet philosophical debate often seems to overcomplicate the issue. This article argues that the responsible protection of our rights arises, instead, with a constant reappraisal of citizenship. Freedom and obedience are ultimately two sides of an abacus with objective counters with subjective values; each individual’s calculations must be represented for there to be an accurate model of obligation.
Keywords: Socrates; Politics; Political Theory; Freedoms; Self-preservation; Protection; Rights; Citizenship; Legitimacy; Obligation